The Brand Gestalt And Green Marketing As Part of Achieving Village Tourism Sustainability - Noor, Tubagus Dicky Faldy Syahid; Mulyana, Mumuh (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Brand Gestalt, Green Marketing and Tourism _____1081 Submitted: MAY 2024 Accepted: JULY 2024 Indonesia has many tourist villages that have the potential to be developed and have their characteristics. However, the COVID-19 pandemic has affected tourism, especially tourist villages. Therefore, tourist villages must rise again. As a form of support to create a sustainable tourism village and have a good business. How does the head of the tourism village manager in the developing category in the Java and Bali regions seek to develop a tourist village in their area by creating the establishment of a destination brand, doing green marketing, and, of course, becoming a sustainable tourism village? This research can be regarded as the contribution of a new model that uses other elements and aspects to form a brand destination for a tourist village destination. Keywords: Brand Gestalt, Green Marketing, Village Tourism Sustainability